If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4 + -1(1 + -7) = 10 Combine like terms: 1 + -7 = -6 2x + -4 + -1(-6) = 10 Multiply -1 * -6 2x + -4 + 6 = 10 Reorder the terms: -4 + 6 + 2x = 10 Combine like terms: -4 + 6 = 2 2 + 2x = 10 Solving 2 + 2x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2x = 10 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 10 + -2 2x = 10 + -2 Combine like terms: 10 + -2 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 2x+4x+14x=0 | | 5+1=3-3(X+6)+4X | | 2x+4x=-14x | | 12-5x=4+(4-1) | | 2.45x+1.5=3.7x-2.24 | | 4x-4=3x-26 | | (x+3)(2x+9)+7(x+3)= | | 1/4x3/7 | | 4s^3+24s^2+74s+50=0 | | 8x-1=3x+17 | | 9-(X+5)=7-1 | | QM=Q+9 | | 4(x-2)=35 | | MQ=Q+9 | | (x+2)(x-2)+3=3 | | 4a+5b=9ab | | x^18+x^9+1= | | y=x^4-2x^3-2x+3 | | Z/z-7,5=12,5/10 | | 23=20-2(-4-3W) | | (X+3)(X+3)+3=(X-4)(X-4) | | x^4-x^2-12x-36=0 | | X^2+6x+77=0 | | 5(Y-2)=31 | | 5(8X+5)=65 | | 2x+10=-35-5x | | 3x-5=2/5 | | (20-2z)/3=0 | | -5-2[2x-4(x+7)]-6= | | x-2=15x-74 | | 2(5+3x)=1 | | 5x+3+-x=2x+1+2x+3 |